A computational scheme to predict dynamics in IoT systems by using particle filter. (21st March 2017) - Cuomo, Salvatore; De Michele, Pasquale; Pragliola, Monica
Summary: Extract information from data, coming from the real world, is a very fascinating challenge. In the Internet of Things society, sensors, devices, and tools are able to generate a lot of data that could be used to predict behaviours. In this paper, we propose a computational scheme in which the clustering methodology is used to classify information that are adopted as observations of an evolutionary method. A sampling techniques are used to model the unknown of a dynamical system as a random variable, and available information are interpreted as probability density function. The probability density function is approximated by an ensemble of weighted particles. Finally, by using this methodology, we present results on the forecast and track users' behaviours in 2 real‐world case studios.